Analisis Jalur Pengaruh Kualitas Pelayanan dan Citra Perusahaan Terhadap Loyalitas Nasabah Melalui Kepuasan Nasabah Sebagai Variabel Intervening di Bank BNI Syariah - Fauzi, Fitriah; Putra, Purnama (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2020)
Service quality is the level of excellence expected and control over that excellence is to fulfillcustomer desires. In the service industry such as Islamic banking, service has an important role ingenerating a sense of satisfaction for customers. Customer satisfaction is related to what is expressedby customers about their perceptions and expectations of the services obtained. Customer satisfactioncan also create long-term customer trust that makes customers loyal to the company. This study aimsto analyze the effect of service quality and corporate image on loyalty through customer satisfactionas an intervening variable at Bank BNI Syariah Bekasi Branch. The population used in this studyis Bank BNI Syariah Bekasi Branch. The sample in this study was taken based on the population ofcustomers who save at BNI Syariah at the Bekasi Branch Office as many as 100 respondents. Theanalysis technique in this study is path analysis, which aims to calculate the influence of one or moreindependent variables on other dependent variables. The results showed that the value of servicequality has a positive effect on customer satisfaction. Furthermore, company image has a positiveeffect on customer satisfaction. Furthermore, service quality and company image have a positive effecton customer satisfaction simultaneously. Then customer satisfaction affects customer loyalty.